Analysis of Air Quality Changes and Influencing Factors in Changchun during the COVID-19 Pandemic in 2020 - Hanbo Gao; Ju Wang; Tongnan Li; Chunsheng Fang (Aerosol and Air Quality Research)
Abstract To study the air quality changes during the Corona Virus Disease 2019 (COVID-19) lockdown in Changchun, we analyzed the changes in pollution of six major pollutants (PM2.5, PM10, SO2, NO2, O3, CO) and correlated them with meteorological parameters, using meteorological data and pollutants concentration data. Regional transport pathways and potential source areas of pollutants were analyzed using the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model and Potential Source Contribution Function (PSCF). The results showed that the concentrations of PM2.5, PM10, SO2, NO2, CO were 30.5%–53.8% lower in the Level I period and 49.4%–65.0% lower in the Level II period than in the pre-lockdown period, respectively. Conversely, O3 increased 59.6% and 58.1% during Level I and Level II, respectively, compared to the pre-lockdown period. During the 55-day lockdown, daily average concentrations of each pollutant were lower than in previous years on 36–55 days, while O3 was higher on 35 days. The pollutants that decreased in concentration during the lockdown also showed an increase during the Level III period (up to 188.5%). The maximum daily growth rate of PM2.5 during the lockdown period in 2020 was 16.0%, which was higher than this value in the same period of previous years (21.8%, 21.4%, 17.4%). This shows that the change trend of pollutants during the lockdown period is smoother than in previous years. Temperature and O3 were positively correlated before the lockdown and during Level I and weakly negatively correlated during Level II and Level III. Despite the prevalence of northwest winds in winter, a high percentage of trajectories from other directions (up to 36.8%) was observed during the lockdown. Simultaneously, the lockdown reduced the potential source area for PM2.5 (WPSCF ≥ 0.000007), but rebounded after the lockdown was lifted. In conclusion, the lockdown only temporarily reduced the air pollution in Changchun.